The leader AZIMUTH check : factor structure of common competencies - Steele, John P.; Garven, Sena.; U.S. Army Research Institute for the Behavioral and Social Sciences (Alexandria, Va. : U.S. Army Research Institute for the Behavioral and Social Sciences, 2009)
"Enhancing the leadership skills of Soldiers is of primary importance to the U.S. Army. A critical step in the process of leader development is self-awareness through self-assessment. Such insight is important because identifying and assessing trainable competencies that facilitate maximum leadership effectiveness creates a strategic advantage. This report describes the psychometric properties and common competencies assessed by the Leader AZIMUTH Check, a 360-degree feedback instrument for Army leaders. The AZIMUTH was designed and implemented by the Army Research Institute (ARI) to improve leader common competency development, leader-directed feedback, and enhance leader self-awareness. The purposes of the present research project were to establish a factor structure of common competencies, the minimum number of raters required for adequate reliability, conceptual agreement across rating sources, rating patterns and behaviors, and validity evidence of the AZIMUTH."--DTIC
"Army project number 622785A790."
"June 2009."
Cover title.
Includes bibliographical references.
Also issued electronically via World Wide Web.
Mode of access: Internet.
Keywords: United States. -- Army; Psychological tests; Reliability; Awareness; Leadership; Ability; Psychometrics; Psychology; Management